Morbidity Pattern among Elderly Population of Changu Narayan Municipality, Bhaktapur - Manandhar, Naresh; Joshi, Sunil Kumar (Journal of Nepal Health Research Council, 2019)
Background: The Senior Citizens Acts 2063, Nepal defines the senior citizens (elderly population) as “people who are 60 years and above”. Health is the most important determinant of the quality of life of people. Ill-health becomes a major obstacle for the well-being of the elderly population. This study was conducted to assess the morbidity pattern in elderly population.Methods: A community based cross-sectional study was carried out in field practice area of the Department of Community Medicine. 124 elderly population were selected by convenient sampling technique. A structured questionnaire was used to collect the data. Data was analyzed using SPSS version 20. Chi-square was used to test the association and p<0.05 was considered as significant.Results: The mean age of elderly population was 69.85 years. Majority (47.6%) of them were in the age group of 60-69 years. Males (50.8%) were more than females (49.2%). Twelve respondents (9.7%) were not suffering from any form of morbidity. Most common morbidity was muscular skeleton problem (40.8%), followed by hypertension (36.3%), diabetes (29.8.8%), psychological (23.4%) and respiratory (18.6%). Other morbidities gastrointestinal, dental, ENT, eye and genitourinary system were found in around ten percentage of elderly population Conclusions: Majority of the elderly population were suffering from non-communicable diseases. There is a need for health care services at all level with special focus on disease prevention, early detection and treatment for elderly population. This study found high prevalence of musculoskeletal, hypertension, diabetes and psychological problem and low prevalence of respiratory, gastrointestinal, dental, ENT, genitourinary and eye problem. Keywords: Changu Narayan; diabetes; hypertension; masculo skeleton; morbidity pattern; senior citizens.